Levantamento etnobotânico de plantas medicinais em quintais urbanos de Benjamin Constant, Alto Solimões-AM - Dias, Matheus de Souza (Brasil, 2025)
Agroforestry backyards (AFBs) are characterized as a traditional land use system used by families living in rural, peri-urban and urban areas. They are usually located close to the home and are managed by family labor, with a prominent presence of women. Medicinal plants are commonly found in urban backyards and have been used to treat various diseases. Many people seek healthier therapeutic alternatives in medicinal plants, with fewer side effects and low cost. The relevance of this study lies in the contribution of urban backyards to the conservation of local biodiversity, allowing the cultivation of medicinal plants, which promotes a better quality of life for those who maintain them. The work was developed in the municipality of Benjamin Constant, which is located in the Southwest Mesoregion of the State of Amazonas, in two neighborhoods of the city, Colônia and Coimbra, located in the urban area of the city. The target audience was residents of the urban area of the city, who have species of medicinal plants in their backyards. An ethnobotanical survey of medicinal plants cultivated and used in these urban backyards was conducted. Semi-structured interviews were conducted with 20 participants, resulting in the identification of 40 species of medicinal plants, distributed in 22 botanical families. The leaves were the parts most frequently used in therapeutic preparation. Among the main indications for use, treatments for diseases of the digestive system, flu symptoms and urinary tract pain stand out. Teas were identified as the most common form of preparation of home remedies. The results demonstrate the extensive traditional knowledge of the residents about the use of medicinal plants and reinforce the cultural and therapeutic importance of these plants in urban backyards in the municipality of Benjamin Constant-AM.